Transcriptional Regulation of Pine Male and Female Cone Initiation and Development: Key Players Identified Through Comparative Transcriptomics - Fritsche, Steffi; Rippel Salgado, Leonardo; Boron, Agnieszka K.; Hanning, Kyrin R.; Donaldson, Lloyd A.; Thorlby, Glenn (Frontiers in Genetics, 2022)
With long reproductive timescales, large complex genomes, and a lack of reliable reference genomes, understanding gene function in conifers is extremely challenging. Consequently, our understanding of which genetic factors influence the development of reproductive structures (cones) in monoecious conifers remains limited. Genes with inferred roles in conifer reproduction have mostly been identified through homology and phylogenetic reconstruction with their angiosperm counterparts. We used RNA-sequencing to generate transcriptomes of the early morphological stages of cone development in the conifer species Pinus densiflora and used these to gain a deeper insight into the transcriptional changes during male and female cone development. Paired-end Illumina sequencing was used to generate transcriptomes from non-reproductive tissue and male and female cones at four time points with a total of 382.82 Gbp of data generated. After assembly and stringent filtering, a total of 37,164 transcripts were retrieved, of which a third were functionally annotated using the Mercator plant pipeline. Differentially expressed gene (DEG) analysis resulted in the identification of 172,092 DEGs in the nine tissue types. This, alongside GO gene enrichment analyses, pinpointed transcripts putatively involved in conifer reproductive structure development, including co-orthologs of several angiosperm flowering genes and several that have not been previously reported in conifers. This study provides a comprehensive transcriptome resource for male and early female cone development in the gymnosperm species Pinus densiflora. Characterization of this resource has allowed the identification of potential key players and thus provides valuable insights into the molecular regulation of reproductive structure development in monoecious conifers.